Binary Cyclic Pearson Codes - Ari Dwi Hartanto; Al. Sutjijana (Jurnal Matematika MANTIK, 2021)
The phenomena of unknown gain or offset on communication systems and modern storages such as optical data storage and non-volatile memory (flash) becomes a serious problem. This problem can be handled by Pearson distance applied to the detector because it offers immunity to gain and offset mismatch. This distance can only be used for a specific set of codewords, called Pearson codes. An interesting example of Pearson code can be found in T-constrained code class. In this paper, we present binary 2-constrained codes with cyclic property. The construction of this code is adopted from cyclic codes, but it cannot be considered as cyclic codes.